2014
DOI: 10.1128/mbio.01710-14
|View full text |Cite
|
Sign up to set email alerts
|

Pneumolysin Activates Macrophage Lysosomal Membrane Permeabilization and Executes Apoptosis by Distinct Mechanisms without Membrane Pore Formation

Abstract: Intracellular killing of Streptococcus pneumoniae is complemented by induction of macrophage apoptosis. Here, we show that the toxin pneumolysin (PLY) contributes both to lysosomal/phagolysosomal membrane permeabilization (LMP), an upstream event programing susceptibility to apoptosis, and to apoptosis execution via a mitochondrial pathway, through distinct mechanisms. PLY is necessary but not sufficient for the maximal induction of LMP and apoptosis. PLY’s ability to induce both LMP and apoptosis is independe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 73 publications
5
53
0
Order By: Relevance
“…However, RAW264.7 cells were resistant to PLY-induced cell lysis. Although RAW264.7 cell may not accurately reflect characteristics associated with human macrophages, human monocyte-derived macrophages isolated from whole blood are also resistant to PLY-induced cell lysis33, which was consistent with our experimental findings. While no studies have so far reported PLY-induced cytolytic activity on alveolar macrophages, our findings suggested that infiltrated neutrophils are the primary target cells of PLY.…”
Section: Discussionsupporting
confidence: 89%
“…However, RAW264.7 cells were resistant to PLY-induced cell lysis. Although RAW264.7 cell may not accurately reflect characteristics associated with human macrophages, human monocyte-derived macrophages isolated from whole blood are also resistant to PLY-induced cell lysis33, which was consistent with our experimental findings. While no studies have so far reported PLY-induced cytolytic activity on alveolar macrophages, our findings suggested that infiltrated neutrophils are the primary target cells of PLY.…”
Section: Discussionsupporting
confidence: 89%
“…Other physiological examples of LDCD include the homeostatic responses of immune cells to infection. In Legionella and Streptococcus pneumoniae infections, the termination of productive infection can give rise to macrophage cell death triggered by cathepsin‐dependent cell death . Viruses have also evolved mechanisms to hijack cellular defenses to their own benefit.…”
Section: Ldcd: Mechanism and Examplesmentioning
confidence: 99%
“…pneumoniae was also shown to trigger LMP and apoptosis of host macrophages (Bewley et al, ). The involved mechanism is complex and partially requires the pneumolysin toxin but not its pore‐forming activity, as well as additional bacterial factors (Bewley et al, ). This mechanism differs from the one observed in our study in epithelial cells, which strictly requires PLY pore‐forming activity (Figure b).…”
Section: Discussionmentioning
confidence: 99%